Estimation of drought resilience potential of rice genotypes: A PEG-based evaluation - Rabnawaz, Maria; Hanif, Alvina; Farooq, Muhammad Shahbaz; Javaid, Rana Arsalan; Arshad, Muhammad; Majeed, Abid (Journal of Pure and Applied Agriculture, 2024)
Rice is a crucial global staple food grown in various climates. However, the increasing scarcity of freshwater resources poses a significant challenge to rice production. Drought, a consequence of climate change, is a main problem to rice yield, affecting its yield significantly. This study evaluated drought tolerance in 25 rice genotypes in a research trial AYT-3 using various concentrations of Polyethylene Glycol (PEG) as an osmotic stress inducer. Results indicated significant variations in drought tolerance index among the genotypes. Notably, AYT 3-9 exhibited the highest root length stress tolerance index (RLSTI), AYT 3-22 displayed the highest shoot length stress tolerance index (SLSTI), and AYT 3-24 showed the highest plant fresh weight stress tolerance index (PFWSTI). Root properties and growth were essential for drought resilience, with deep and extensive root systems contributing to tolerance. However, leaf growth was reduced due to restricted water potential under drought stress. While germination stress tolerance index (GSTI) did not vary significantly, the study highlighted the importance of early germination evaluation in drought tolerance assessment. Genotypes resilient to 15% PEG concentration may be suitable for breeding programs to develop drought-tolerant rice cultivars. This research emphasized the potential of early screening techniques to select genotypes with superior drought tolerance, essential for ensuring food security in regions vulnerable to water scarcity.